Research Brief No. 13 - The Social and Health Service Needs of Aboriginal Peoples in Urban Southern Ontario - Cooke, Martin; Woodhall, Julia; McWhirter, Jennifer (Scholarship@Western, 2016)
The disproportionate needs of urban Aboriginal people make it important for urban social and health service providers to understand the conditions faced by this population. This synthesis paper reviews recent literature on urban Aboriginal populations in order to identify their characteristics and main areas of need. It is meant to inform those who work in health and social service planning and delivery in smaller urban centers, particularly non-Aboriginal service agencies in Southern Ontario. The existing research shows that urbanized First Nations, Métis and Inuit have greater needs for specific health, cultural, justice, financial, and educational services. Further-more, the literature indicates that it is important that these services are provided in a way that respects, includes, and promotes pride in Aboriginal cultures and histories.